Nursing care for hematopoietic stem cell transplant recipients and their families - Isabelle Campos de Azevedo; Alexandra do Nascimento Cassiano; Jovanka Bittencourt Leite de Carvalho; Marcos Antonio Ferreira Júnior (Rev Rene)
Objective: to identify nursing care for hematopoietic stem cell transplant recipients and their families. Methods: integrative review with searches in the databases SCOPUS; National Library of Medicine; Web of Science, Cumulative Index to Nursing and Allied Heath Literature and Latin American and Caribbean Literature in Health Sciences. The selected studies were published between 2008 and 2014. Results: 460 articles were initially identified, culminating in the final sample of seven studies analyzed in their entirety. Care provided varied in all studies, from actions directed to health education practices, to the accomplishment of complementary therapies and the implementation of Advanced Nursing Practice with a view to qualification of care. Conclusion: care provided includes health education actions, complementary therapies to promote well-being and quality of life, as well as the implementation of the Advanced Nursing Practice with a view to qualification of care.